Synthesis Gas Production via Aqueous Phase Reforming over Hydrotalcite-supported Catalysts - Luthfiana Nurul Hidayati; Anis Kristiani; Kiky Corneliasari Sembiring; Fauzan Aulia; Sudiyarmanto Sudiyarmanto (Jurnal Kimia Terapan Indonesia, 2021)
Depletion of fossil fuel has gained attention to find an alternative of energy resources. The consumption of fossil fuel is increased gradually, raising many unfavourable challenges such as exploiting the unrenewable resources and causing environmental damages. This study aimed to produce clean energy derived from renewable resources. Glycerol as a by-product from biodiesel production from palm oil through  esterification process. Conversion of glycerol to synthetis gas (syngas) which produced hydrogen as the main product is considered as a renewable-clean fuel. Glycerol has been successfully converted to syngas by Aqueous Phase Reforming (APR) process over solid base catalysts. Hydrotalcite which is a layered double hydroxide used as catalyst support was impregnated with various metal promoters such as Ni, Cu, Co, Zn, and Sn. Those catalysts were characterized by Brunauer-Emmett-Teller surface area analysis, Thermal Gravimetry Analysis, Fourier Transform Infrared Spectrometry and X-Ray Diffraction to investigate the properties and structure of the catalysts. Catalytic activity was evaluated in a continuous fixed- bed reactor to produce syngas through APR reaction. The gas products were analyzed by GC-TCD, resulting Cu/hydrotalcite catalyst produced hydrogen, 55.2% v/v.